Factors Affecting the Change in Cassava Prices of Farmers in Nan District, Luang Prabang Province - phanthouly, vilasith; Siphanthong, Bounthavy; Sioudomphan, Soutthavone (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This research aims to study 1) the production, distribution of cassava among farmers in Nan District, Luang Prabang Province, and 2) the factors affecting the price changes of cassava among farmers in Nan District, Luang Prabang Province. This study used a quantitative research method using a questionnaire with closed and open ends; the target group of the research was 267 households of farmers who produce cassava in Nan District. Descriptive statistics, including frequency values and percentages, and inferential statistics, including multivariate regression with the least squares method, were used to analyze the data using the statistical analysis program SPSS version 27. The study found that: 1) The production conditions of farmers in Nan District, Luang Prabang Province, choose to grow cassava because cassava can be easily grown and maintained, produces a lot of yield, and has a market for it. They learned about cassava cultivation from neighbors, from cassava growers' groups, and from online and have been growing cassava for 2 years. In an area of ​​between 1-3 hectares, the average annual planting cost is about 10,000,000 kip, and the yield is more than 20 tons/year; for distribution and price changes, most of the cassava is sold as raw cassava, which is sold at a price of 800 - 2000 kip/kg. Most of the cassava is sold to factories or companies and middlemen; the rest is sold by itself at the market. 2) Factors affecting cassava prices There were 7 factors: cassava cultivation costs, cassava distribution costs, cassava product quality, market demand, and government policies, which resulted in the increase of cassava prices for farmers by 1.429%, 0.285%, 0.447%, 1.790%, and 1.170%, respectively; while cassava production volume and market supply resulted in the decrease of cassava prices for farmers by 0.126% and 1.572%, with a statistical significance level of 0.01.